Special tax scheme for Malaysia’s social enterprise: An incentive for public good - Radzi, S.N.M.; Rahim, S.A.; Zainol, N.R.; Abd Ghadas, Z.A.; Mansyar, M.; Daud, R.R.R. (2021)
Social enterprise operations are always associated with the dual mission, i.e. social mission and profit orientation. These two missions are embedded as a mechanism for combating social problems through innovative approach in the organization of social enterprises. Social enterprise operates in Malaysia through different form business entities, such as partnership, company, and limited liability partnership. Social entrepreneurs will have the capacity through these business enterprises to produce their own profit and profits without relying on the government. Although their primary purpose is to serve social needs, Malaysia's social enterprise denies the benefit of tax exemption as applied to charities. These are being also levied on other private business companies with high rate taxes. The goal of this paper is therefore to explore the possibility of implementing new tax treatment for social enterprise in Malaysia, in order to encourage their involvement in social mission. This paper adopted library research approach combining legal research methodology which mainly involves document analysis such as case law, legal provision and legal theories to see how they might be used to the subject matter.